Reducing post-harvest losses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Grain storage losses in Zimbabwe by M Ketetere and D Giga 1991 101pp ISBN 0850 8526 ENDA, PO Box 3370, Dakar SENEGAL